Genotoxicity Assessment of Multispecies Probiotics Using Reverse Mutation, Mammalian Chromosomal Aberration, and Rodent Micronucleus Tests - Yi-Jen Chiu; Mun-Kit Nam; Yueh-Ting Tsai; Chun-Chi Huang; Cheng-Chih Tsai (The Scientific World Journal)
Genotoxicity assessment is carried out on freeze dried powder of cultured probiotics containing Lactobacillus rhamnosus LCR177, Bifidobacterium adolescentis BA286, and Pediococcus acidilactici PA318. Ames tests, in vitro mammalian chromosome aberration assay, and micronucleus tests in mouse peripheral blood are performed. For 5 strains of Salmonella Typhimurium, the Ames tests show no increased reverse mutation upon exposure to the test substance. In CHO cells, the frequency of chromosome aberration does not increase in responding to the treatment of probiotics. Likewise, the frequency of micronucleated reticulocytes in probiotics-fed mice is indistinguishable from that in the negative control group. Taken together, the toxicity assessment studies suggest that the multispecies probiotic mixture does not have mutagenic effects on various organisms.